Academic Motivation and Self- Efficacy as Predictors of Academic Performance Among form Three Students in Kitui County, Kenya (International Journal of Scientific Research and Management (IJSRM), 2021)
Poor academic performance in national examinations in Kenya like in most countries has been an issue of concern. Poor academic performance has been attributed to school environmental factors with individual psychological factors receiving little attention yet this may contribute towards poor students’ academic performance. In addition to this, most of the studies that have explored psychological factors have been done in developed countries hence leaving a gap locally. The purpose of the study was therefore to examine if self-efficacy and motivation predicts academic performance and if so, to what extent. Academic performance was the outcome variable while the predictor variables was motivation and self-efficacy. The objectives of the study were to examine the relationship between motivation and academic performance, establish the relationship between self-efficacy and academic performance, to determine the relative predictive weights of motivation and self-efficacy on academic performance and lastly to test for gender differences in academic motivation and self-efficacy. Self-determination theory by Ryan and Deci and Social Learning Theory by Bandura guided the study. Data was collected through use of questionnaires which also gave students biographical information. The researcher employed ex post facto design and involved 193 study participants. Out of 31 public secondary schools in Kitui County, 25% of the schools were sampled for this study. Stratified random sampling procedure was used to select the study sample, 8 schools were selected to participate in the study, and 24 students were randomly selected from each secondary school. A pilot study was carried out on a random sample of 40 students from a public school which was not part of the study sample but of similar characteristics as sampled schools. The academic motivation and academic self-efficacy scales were adapted to measure academic motivation and self-efficacy. Students’ academic performance was measured by use of examination records which was obtained from the schools. Pearson product moment correlation coefficient was used to test relationships between variables while multiple regression analysis tests were used to obtain the relative predictive weights of independent variable on outcome variable and t-test for predictor variables for gender. Data was analyzed by use of descriptive and quantitative statistics. This research may be of importance to the educators as they may understand how these psychological predictors may impact on their students. Secondly, the teachers may be able to gauge their students’ motivation and self-efficacy which may help them in setting realistic targets for performance. Understanding motivation and self-efficacy may enable schools reach operational efficiency as teachers will be in a position to address students according to their study requirements. In view of the findings, it can be inferred that academic motivation, self-efficacy and academic performance are statistically dependent as the p-value in the ANOVA model was .000 which is less than 0.05, the alpha level of significance for academic and self-efficacy and academic performance (R (192) =0.367. The study recommended that all stakeholders in education should work together in creating conducive environments for development of academic motivation and self-efficacy, among students and appropriate intervention programmes should be developed in schools, particularly targeting girls in order to help reduce the gender differences which were found to exist with regard to students’ academic motivation and self-efficacy learning.